Microfinance Investment in Sub-Saharan Africa : Turning Opportunities into Reality - Glisovic, Jasmina (Washington, DC: World Bank, 2012)
Yet despite healthy economic prospects, the region has the lowest share of banked households in the world (12 percent) and the highest share of poor people, with 50 percent of the population living on $1.25 a day or less (Consultative Group to Assist the Poor, or CGAP and World Bank 2010). More work needs to be done to expand financial access, and many governments and international funders are keen to contribute. Equity and debt capital continues to be important in developing financial services for low-income populations in the region. However, local equity is not available in most countries, and local debt funding is scarce. Sub-Saharan Africa (SSA) microfinance relies heavily on deposit funding, mostly composed of short-term deposits, while many smaller institutions cannot attract sufficient deposits to finance growth. The region received 11 percent of global microfinance funding commitments in 2010.4 In terms of cross-border investment, it received among the lowest levels in the world, $1 billion out of a total of $13 billion as of December 2010 (Reille, Forster, and Rozas 2011). This brief examines public and private foreign investment in SSA microfinance retailers, and the key challenges that limit investment. The findings are based on CGAP data on cross-border funding flows, publicly available resources, and interviews with more than 30 investors and other stakeholders conducted in the first quarter of 2012.